Bioactive Silk Revolution: Harnessing Curcuminoid Dye and Chitosan for Superior Antimicrobial Defence and UV Shielding - Khai Ly Do; Taswar Ahsan; Abdul Wahab; Muhammad Tayyab; Xinqi Yin; Nengjie Pan; Tao Huang; Asim Mushtaq; Miao Su (Pharmaceutics)
Background/Objectives: The use of natural colourants is gaining attention due to their biocompatibility and functional benefits. This study introduces a different approach using turmeric (Curcuma longa L.) dye extract combined with chitosan to significantly enhance the antibacterial and UV-shielding properties of silk. Methods: The turmeric dye’s chemical composition was analyzed using liquid chromatography mass spectrometry (LC-MS), UV–visible spectroscopy, and Fourier-transform infrared spectroscopy (FTIR). The dyed silk’s colourfastness was tested through rubbing, washing, and light exposure. Results: The chitosan-mordanted silk showed strong antibacterial activity against Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus), as well as antifungal activity against Aspergillus niger (A. niger). It also demonstrated a high ultraviolet protection factor (UPF). For comparison, alum-mordant was used, and chitosan proved more effective. Beyond its use as a dye, turmeric is renowned for its medicinal properties. Its antioxidant, anticancer, and anti-inflammatory properties have been extensively researched, which are primarily linked to its curcuminoid compounds. Turmeric is used in traditional medication to treat digestive issues, arthritis, and skin diseases. Conclusions: This work underscores the innovative use of plant-based dye extracts and natural mordants like chitosan as a sustainable alternative to conventional metallic mordants, paving the way for the evolution of bioactive silk with improved functional properties.